ENRICHING THE QUALITY OF EDUCATION IN UZBEKISTAN AND STRENGTHENING THE LEGAL FRAMEWORK - S.E.Suyarova; N.K.Ravshanova; L.G.Yakubova; Sh.S.Abdullaeva (Research Parks Publishers, 2020)
This article summarizes information on improving the quality of education and creating a legal framework in Uzbekistan. It also systematically highlights the changes and updates taking place at all stages of the continuing education system